Epstein-Barr Virus in Burkitt Lymphoma in Africa Reveals a Limited Set of Whole Genome and LMP-1 Sequence Patterns: Analysis of Archival Datasets and Field Samples From Uganda, Tanzania, and Kenya - Liao, Hsiao-Mei; Liu, Hebing; Chin, Pei-Ju; Li, Bingjie; Hung, Guo-Chiuan; Tsai, Shien; Otim, Isaac; Legason, Ismail D.; Ogwang, Martin D.; Reynolds, Steven J.; Kerchan, Patrick; Tenge, Constance N.; et al. (Frontiers in Oncology, 2022)
Epstein-Barr virus (EBV) is associated with endemic Burkitt lymphoma (eBL), but the contribution of EBV variants is ill-defined. Studies of EBV whole genome sequences (WGS) have identified distinct phylogroups that appear to be distinct for Asian versus non-Asian EBV sequences, but samples from BL or Africa, where EBV was first discovered, are under-represented. We conducted a phylogenetic analysis of EBV WGS and LMP-1 sequence obtained primarily from BL patients in Africa and representative non-African EBV sequences from other conditions or regions using data from GenBank, Sequence Read Archive, or Genomic Data Commons for the Burkitt Lymphoma Genome Sequencing Project (BLGSP) to generate data to support the use of a simpler biomarker of geographic or phenotypic association. We also investigated LMP-1 patterns in 414 eBL cases and 414 geographically matched controls in the Epidemiology of Burkitt Lymphoma in East African children and minors (EMBLEM) study using LMP-1 PCR and Sanger sequencing. Phylogenetic analysis revealed distinct genetic patterns of African versus Asian EBV sequences. We identified 281 single nucleotide variations (SNVs) in LMP-1 region, which formed 12 unique patterns (A to L). Nine patterns (A, AB, C, D, F, I, J, K and L) predominated in African EBV, of which four were found in 92% of BL samples (A, AB, D, and H). Predominant patterns were B and G in Asia and H in Europe. EBV positivity in peripheral blood was detected in 95.6% of EMBLEM cases versus 79.2% of the controls (odds ratio [OR] =3.83; 95% confidence interval 2.06-7.14). LMP-1 was successfully sequenced in 66.7% of the EBV DNA positive cases but in 29.6% of the controls (ORs ranging 5-11 for different patterns). Four LMP-1 patterns (A, AB, D, and K) were detected in 63.1% of the cases versus 27.1% controls (ORs ranges: 5.58-11.4). Dual strain EBV infections were identified in WGS and PCR-Sanger data. In conclusion, EBV from Africa is phylogenetically separate from EBV in Asia. Genetic diversity in LMP-1 formed 12 patterns, which showed promising geographic and phenotypic associations. Presence of multiple strain infection should be considered in efforts to refine or improve EBV markers of ancestry or phenotype.